The PI3K/Akt Signaling Pathway Mediates the High Glucose-Induced Expression of Extracellular Matrix Molecules in Human Retinal Pigment Epithelial Cells - Dong Qin; Guo-ming Zhang; Xun Xu; Li-ya Wang (Journal of Diabetes Research)
Prolonged hyperglycemia is an important risk factor of the pathogenesis of diabetic retinopathy (DR). Extracellular matrix molecules, such as fibronectin, collagen IV, and laminin, are associated with fibrotic membranes. In this study, we investigated the expression of fibronectin, collagen IV, and laminin in RPE cells under high glucose conditions. Furthermore, we also detected the phosphorylation of protein kinase B (Akt) under high glucose conditions in RPE cells. Our results showed that high glucose upregulated fibronectin, collagen IV, and laminin expression, and activated Akt in RPE cells. We also found that pretreatment with LY294002 (an inhibitor of phosphatidylinositol 3-kinase) abolished high glucose-induced expression of fibronectin, collagen IV, and laminin in RPE cells. Thus, high glucose induced the expression of fibronectin, collagen IV, and laminin through PI3K/Akt signaling pathway in RPE cells, and the PI3K/Akt signaling pathway may contribute to the formation of fibrotic membrane during the development of DR.